(untitled) (Научни трудове на УНСС, 2020)
Youth unemployment is a serious problem with both economic and social nature. On the one hand, it represents unused in the national economy resource, on the other, the limited opportunity for a younger population to achieve social inclusion through participation in the economic life through production and consumption. The present study examines youth unemployment in Bulgaria as a function of the problems in a several public systems. The report proposes methods of collaboration between policies at national level and initiatives at regional and local level, aimed to effectively increase youth employment.